Electrical reliability of ultra-low k dielectric of an IC device of its optical spectroscopic characterization - Lam, Jeffrey Chor Keung (2014)
In summary, electrical reliability of ultra-low k dielectrics of leading edge semiconductor Integrated circuits (IC) was investigated using complimentary vibrational spectroscopy of Raman and Fourier Transform Infra-Red (FTIR). In order to reduce the resistance and capacitance (RC) delay in advanced semiconductor IC process, Cu and ultra-low k dielectric was introduced to replace aluminum (Al) and silicon dioxide (SiO2) as metal interconnects and inter-metal dielectrics, respectively. However, low k and ultra-low k dielectric reliabilities become a concern due to their weak mechanical strength and chemical bonding. In this project, time dependent dielectric breakdown (TDDB) failure of ultra low- k dielectrics is investigated. TDDB is the standard for low k dielectric reliability stress test. There are several TDDB studies carried out to investigate the mechanism of TDDB failure of low k dielectrics. The complementary vibrational spectroscopy techniques, Raman and FTIR spectroscopy, were used to investigate the failure mechanism of the TDDB failure. These techniques can obtain the information of the molecular bonding and structure in low k dielectrics. Many researchers have investigated characteristics of low k or ultra-low k dielectrics on blank wafers. However, little research involves Raman and FTIR analysis on low k and ultra-low k dielectric in realistic IC devices. Hence, in TDDB analysis, the mechanism is still arguable and damage of the low k dielectric in TDDB test is uncertain. Raman and FTIR spectroscopy could be one of the most promising techniques to identify the chemical bonding change during TDDB stress test. In this work, a methodology to study SiCOH low k/ultra-low k dielectric thin films on patterned wafers by overcoming technique limitation of Raman and FTIR spectroscopy due to the fluorescence in Raman spectroscopy and weak signal from patterned Cu/ultra-low k structures, has been developed. Ultra-low k dielectric TDDB process is characterized using complementary Raman and FTIR vibrational spectroscopy. Under the applied electrical field, the ultra-low k dielectric would first degrade. Ta ions would then migrate into ultra-low k along interfacial weakness of Cu/Ta/TaN/SiCOH, resulting in a more severe damage to the ultra-low k dielectric. The Ta ions inside the ultra-low k induced an increased local electrical field between Cu electrodes and thus accelerated the ultra-low k degradation to final breakdown. No out-diffusion of Cu ions is observed. For the first time, a new TDDB failure mechanism based on Ta/TaN barrier metal migration which occurred some distance away from capping layers is proposed. The pores in ultra-low k materials were degraded under high electrical field, resulting in the Ta ionic migration into the degraded inter-metal dielectric (IMD). This failure mechanism fits well to the “square root of E” √(E )model. Additionally, wafers with Reactive ion etching (RIE) etch experiments are devised to explore the line edge roughness (LER) effect on TDDB. A unified model and understanding for the spacing variations is established. In summary, we can see that more dense Ultralow k dielectric material, a better slopped trench/via profile and more tightened control on metal roughness are needed for a robust ultra-low k TDDB performance.